(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This article is part of the theme urban issues based on a qualitative study conducted in the neighborhood of Santa Cruz, West Zone of the municipality of Rio de Janeiro. To introduce discussions related to spatial organization, we traced a mapping of cultural collectives and the actions of these groups in the neighborhood.Study on the practices of peripheral youth, organized in cultural collectives, for the cultural expression and reinvention of space. Thus, the research is structured in sections that cover the investigative question - what is the role of cultural collectives in the spatial organization of a peripheral neighborhood?- In the first section, we discuss the relationship between peripheral subjects and action in cultural collectives. In the second, a documentary research focuses on the profile of The Youth of Santa Cruz. In the third, a mapping of the collectives that work in the neighborhood. In the end considerations of the spatial organization of the Neighborhood of Santa Cruz and the actions of cultural collectives.